THE IMPORTANCE OF ENRICHING CONFECTIONERY PRODUCTS WITH VITIMAN AND MINERALS - Barnokhon Sattarova; Maxmudova Aziza; Utanova Nazira (International Engineering Journal For Research & Development, 2022)
In this article we will talk about the methods of producing useful confectionery products for the human body